Test results of insecticides from the chemical class of anthranyldiamides on cucumbers in greenhouse - F. B. Musaev; A. I. Tareev; N. P. Vershinina (Овощи России, 2022)
Relevance. The adaptive-integrated plant protection system is the basis of biologized protective measures against harmful organisms. This system provides for careful treatment of natural resources, prevents contamination of soil and water with pesticides and agrochemicals. In recent years, legislation and sanitary regulations have increasingly tightened the regulations governing the use of pesticides in crop production. Organic farming is becoming increasingly common. Leading global chemical companies are expanding their research on the biology of manufactured plant protection products: they give them a selective character, reduce the period of their inactivation, respectively, the waiting period. FMC manufactures and supplies to Russia new generation insecticides Verimark® and Benevia® from the chemical class of diamides compatible with the biomethode and having a short waiting time.Methods. In 2020-2021, in the greenhouse complex of the FSVC, an assessment of the biological effectiveness of the insecticides Verimark® and Benevia® on cucumber culture has been carried out. Verimark® was applied by shedding seedlings under the root and applying through a drip system, Benevia® was introduced by ground spraying of vegetating plants.Results. The most problematic cucumber pests in greenhouse are tobacco trips (Thrips tabaci) and greenhouse whitefly (Trialeurodes vaporarium). As a result of successive additions of the Verimark® (for the root) and Benevia® (for the leaves), the number of tobacco thrips was reduced by 90,8-98,9%. Spraying the plants with Benevia® in admixture with Codacide oil also provided a high positive effect against the greenhouse whitefly. Already on the third day, the number of pests decreased by 90,3%. Protective measures made it possible to increase crop yield by 26.3% in the first turnover and 28.3% in the second. The highest rates of biological efficacy were observed in the use of preparations before the start of pest settlement, which is fully supported by the recommendations of the manufacturer.